Skin infection on both legs caused by Acremonium strictum (case report) - Hilmioglu, Suleyha (Ann Saudi Med, 2015)
Acremonium species are saprophytic molds widely distributed in nature, existing in soil and decaying vegetation. Penetrating wounds, intravascular catheters and immunosuppression are risk factors for invasive infections of Acremonium. The fungus can also cause cutaneous infections and mycetoma in the immunocompetent; such infections occur in extremities open to trauma. In this paper, a female patient with skin infection due to Acremonium strictum in both legs is described.